Effect of Vitis gracilis Wall. administration on maximal swimming exercise apoptosis via cytochrome c in rat lung cells - Putra Santoso; Syafruddin Ilyas; Yurnadi Hanafi Midoen; Putri Cahaya Situmorang (GarVal Editorial Ltda., 2023)
Context: The high mortality rate in people with lung disease indicates that this disorder requires immediate attention. It is established that excessive swimming can reduce the ability of lung cells to function and cause respiratory problems. Vitis gracilis Wall. is a traditional medicinal plant used by the Karo people of North Sumatra to improve stamina. Aims: To analyze apoptosis via cytochrome c in serum and lung tissue after V. gracilis administration. Methods: Rats that experienced excessive physical activity received six different treatments: two groups as negative and positive control groups, one vitamin C control group, and three groups orally administered with ethanolic extract of V. gracilis leaves at different doses. Immunohistochemistry, ELISAs, and TUNEL assays were used to assess study parameters. Results: There were significant differences (p<0.05) in the expression of cytochrome c and apoptotic cells in the lung. Excessive swimming can increase TNF-α levels and decrease interleukin-10 (IL-10) in rats, but administration of V. gracilis produced nearly identical results to the positive control group and was not significantly different to the vitamin C group, indicating that V. gracilis was effective in reducing TNF-α levels and increasing IL-10. Conclusions: Excessive swimming in rats can increase cytochrome c expression and apoptosis, whereas V. gracilis can reduce apoptosis that occurs via the intrinsic pathway through cytochrome c expression in the lungs.